Para Clinical Studies of Ethanol Extract of Achillea millefolium L. on Electrocardiogram, Cardiac Enzymes and Serum Electrolytes in Sheep - R Rahchamani; MR Mokhberdezfoli; A Hadjiakhoondi; A Raoofi; Sh Rezazadeh; E Banihasan; H Sharifi; Z Nazem Bokaee (Institue of Medicinal Plants, ACECR, 2008)
Background: Achillea millefolium has been used for centuries in traditional medicine. It has many indications including treatment of heart weakness, hypertension cerebral and coronary thrombosis in traditional system of medicine. Objective: The purpose of this study is an investigation on effects of Achillea millefolium total extract on electrocardiogram, cardiac enzymes and serum electrolytes in sheep. Method: In this study, 12 clinically healthy sheep were divided into 2 groups of treatment and control. The treatment group were administered intravenously a total extract of Achillea millefolium in the dose of 20 mg/kg. The control group received normal saline. Base-apex electrocardiogram was recorded in 0, 5, 15, 30, 45, 60, 90 and 120 minutes after administration and blood samples were collected in 0, 2, 6, 24, 48 and 72 hours after administration. Serum cTnT, CK-MB, AST, Na, P, K, Ca, Mg and Cl were measured. Results: Total extract of Achillea millefolium significantly (p<0.05) increased P amplitude after 5 and 90 minutes and S amplitude after 120 minutes and decreased T duration after 15 minutes following administration. Achillea millefolium had no significant effect on serum enzymes and electrolytes. Conclusion: Regarding that Achillea millefolium extract increased cardiac contractility after 2 hours, detailed studies on the active constituents are needed which might provide new insight in cardiovascular drugs.